PENERAPAN COOPERATIVE LEARNING TIPE STAD BERBANTUAN MIND MAP CANVA TERHADAP PENINGKATAN HASIL BELAJAR IPS - Atila Zifa Yulestian; Lukki Lukitawati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study was motivated by the low level of student engagement and learning outcomes in social studies (IPS) learning, which is still dominated by conventional teaching methods. The research aimed to examine the effect of implementing the Student Teams Achievement Divisions (STAD) cooperative learning model assisted by Canva-based mind mapping on improving students’ learning outcomes in the topic of Population Dynamics for eighth-grade students at SMP N 12 Semarang. The study employed a quantitative approach using a Quasi-Experimental Non-equivalent Control Group Design. The sample consisted of two classes selected through purposive sampling, namely class VIII B as the experimental group and class VIII C as the control group, each comprising 31 students. The research instrument was a validated and reliable achievement test (Cronbach’s Alpha = 0.950). Data were analyzed using normality and homogeneity tests, Independent Sample t-Test, and N-Gain analysis. The results revealed a statistically significant difference in learning outcomes between the experimental and control groups, with a Sig. (2-tailed) value of 0.034 < 0.05. The N-Gain score of the experimental class was 0.83, while that of the control class was 0.82, both categorized as high, although the experimental group demonstrated a more optimal improvement. Therefore, the implementation of the STAD model assisted by Canva-based mind mapping has a positive and significant effect on improving students’ social studies learning outcomes. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya keterlibatan dan hasil belajar siswa dalam pembelajaran IPS yang masih didominasi metode konvensional. Penelitian ini bertujuan untuk menganalisis pengaruh penerapan model cooperative learning tipe Student Teams Achievement Divisions (STAD) berbantuan mind map berbasis aplikasi Canva terhadap peningkatan hasil belajar IPS materi Dinamika Penduduk siswa kelas VIII SMP N 12 Semarang. Penelitian menggunakan pendekatan kuantitatif dengan desain Quasi-Experimental Non-equivalent Control Group Design. Sampel penelitian terdiri atas dua kelas yang dipilih melalui teknik purposive sampling, yaitu kelas VIII B sebagai kelas eksperimen dan VIII C sebagai kelas kontrol, masing-masing berjumlah 31 siswa. Instrumen penelitian berupa tes hasil belajar yang telah diuji validitas dan reliabilitasnya (Cronbach’s Alpha = 0,950). Analisis data dilakukan melalui uji normalitas, uji homogenitas, uji Independent Sample t-Test, serta perhitungan N-Gain. Hasil penelitian menunjukkan bahwa terdapat perbedaan hasil belajar yang signifikan antara kelas eksperimen dan kelas kontrol dengan nilai Sig. (2-tailed) sebesar 0,034 < 0,05. Nilai N-Gain pada kelas eksperimen sebesar 0,83 dan kelas kontrol sebesar 0,82 yang keduanya berada pada kategori tinggi, namun kelas eksperimen menunjukkan peningkatan yang lebih optimal. Dengan demikian, penerapan model STAD berbantuan mind map Canva berpengaruh positif dan signifikan terhadap peningkatan hasil belajar IPS siswa.